Social values priorities and orientation towards individualism and collectivism of Greek University students - Papastylianou, Dona (Journal of beliefs and values, 2016)
The study aimed to explore the value priorities of Greek young adults and their orientation towards individualism and collectivism and to investigate for possible relationships between value types and individualism and collectivism. Greek undergraduate students (n = 484) completed the Social Values Survey, the Auckland's Individualism and Collectivism Scale and a form of demographic information. Benevolence, self-direction and hedonism were found to be the most highly rated value types for both males and females. In the case of individualism and collectivism participants scored higher on collectivism. Males and science and technology students scored higher on value types regarding openness to change and self-enhancement. Females and social and humanities students scored higher on conservation and self-transcendence value types. Religiosity was associated to collectivism and to value types regarding conservation and self-transcendence. Regression analysis revealed a direct association between individualism and openness to change and self-enhancement. Collectivism was found to be associated with conservation and self-transcendence.